Unnatural narratives--unnatural narratology - Alber, Jan, 1973-; Heinze, Rüdiger, 1972- (Linguae & litterae ;, 2011)
The study of unnatural narratives has become an important, but still disparate new research program in narrative theory. This collection of essays presents and discusses the new analytical tools that have so far been developed on the basis of unnatural novels, short stories, and plays and extends these findings through analyses of testimonies, comics, graphic novels, films, and oral narratives. Taken together, the essays develop new modeling systems which are designed to capture the strangeness and extravagance of unnatural narratives.